Comparison of first-line treatment with bendamustine plus rituximab versus R-CHOP for patients with follicular lymphoma grade 3A: Results of a retrospective study from the Fondazione Italiana Linfomi - Margiotta-Casaluci, Gloria; Bigliardi, Sara; Cocito, Federica; Meli, Erika; Petrucci, Luigi; Nicolosi, Maura; Annibali, Ombretta; Boccomini, Carola; Bozzoli, Valentina; Castellino, Alessia; Cattina, Federica; Cenfra, Natalia; et al. (Frontiers in Oncology, 2023)
In the setting of follicular lymphoma (FL), frontline therapy with rituximab, cyclophosphamide, doxorubicin, and prednisone (R-CHOP) has represented for many years the standard of care for patients with symptomatic advanced disease. More recently, the combination of bendamustine plus rituximab (R-B) has emerged as an alternative therapeutic option. We present a retrospective, multicenter, observational study aimed at comparing outcomes and toxicities observed in 145 patients diagnosed with grade 3A FL treated with a first line therapy in 15 Italian Fondazione Italiana Linfomi centers between the 1st of January 2014 and the 30th of May 2018. Seventy patients were treated with R-B and 75 with R-CHOP. In the R-B group, the median age at the time of diagnosis was 67 years compared with 59 years in the R-CHOP group. Patients in R-B group achieved a similar overall response rate (96% vs 99%) and a better complete remission rate (87% vs 80%, p = 0.035) compared with patients in R-CHOP group. Progression free survival (PFS) was similar between individual treated with R-CHOP and R-B (48- month PFS 77.7% vs 76.6% respectively, p=0.745). The overall survival was significantly longer with R-CHOP treatment (HR=0.16; 95% IC, 0.04-0.74; p=0.007); however, no statistical significant different was observed after adjustment for age. With the limitations of the study design, our results suggest that both R-B and R-CHOP seem to be valid first-line treatment options in FL3A.